Adjuvant stereotactic body radiotherapy after marginal resection for hepatocellular carcinoma with microvascular invasion: A randomised controlled trial. (May 2022) - Shi, Changying; Li, Yong; Geng, Li; Shen, Weifeng; Sui, Chengjun; Dai, Binghua; Lu, Jiongjiong; Pan, Mianshun; Yang, Jiamei
Abstract: Background: Marginal resection frequently occurred in hepatectomy for hepatocellular carcinoma (HCC), leading to increased local recurrence, especially among patients with microvascular invasion (MVI). Stereotactic body radiotherapy (SBRT) showed effectiveness in controlling tumour and tumour thrombosis. This study aimed to investigate the efficacy of SBRT, targeting on suboptimal resection margin, as adjuvant setting in MVI-positive HCC. Methods: This was a single-centre randomised controlled trial conducted in Eastern Hepatobiliary Surgery Hospital, Shanghai, China. Participants with MVI-positive HCC receiving marginal resection were randomly assigned to the postoperative adjuvant SBRT or surgery alone (SA) group. SBRT was delivered by the CyberKnife® system with marker tracking devices, targeting on resection margin one month after surgery. The disease-free survival (DFS) and overall survival (OS) were compared between the groups, and the adverse events (AEs) were monitored. This trial was registered on ClinicalTrials.gov, NCT04891874. Findings: A total of 76 participants were enrolled, with 38 in each group. The one-, three-, and five-year DFS rates were 92.1%, 65.8%, and 56.1% in SBRT group versus 76.3%, 36.8%, and 26.3% in SA group, respectively ( p  = 0.005). The one-, three-, and five-year OS rates were 100%, 89.5%, and 75.0% in SBRT group versus 100.0%, 68.4%, and 53.7% in SA group, respectively ( p  = 0.053). The total dose of SBRT for single participant was 35 Gy, and the biological effective dose (BED) was 59.5 Gy. The overall incidence of radiotherapy-related AE was 31.6% (12/38), and no grade 3 or higher grade AE was developed. Interpretation: SBRT on the resection margin provides a safe therapeutic modality of adjuvant setting in MVI-positive HCC with suboptimal resection margin. It prevents local recurrence and improves DFS. Trial registration number: NCT04891874. Highlights: Stereotactic body radiotherapy (SBRT) plays an adjuvant role in resected liver cancer. Daily dose of 7 Gy was testified safe in the adjuvant setting for liver. Silver clips marked resection margin were set as the target in SBRT. Local recurrence rate decreased and disease-free survival improved after adjuvant SBRT.